2012
DOI: 10.1002/cpp.1817
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Response in Type 2 Diabetes Patients with Major Depression

Abstract: Findings suggest that Interpersonal Psychotherapy is a useful tool to treat major depression in type 2 diabetes patients. A significant number of type 2 diabetes patients with major depression do not achieve depression remission irrespective of the type of treatment. Further clinical research should focus on addictive effects of psychotherapy and psychopharmacology in the treatment of depressed patients with chronic somatic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 46 publications
0
20
0
1
Order By: Relevance
“…With regard to the effects of HFD, only one study reported that unpredictable chronic mild stress-induced behavioural changes were all reversed by fluoxetine in STD-fed mice but not in HFDfed mice (Isingrini et al, 2010). SSRI non-response in T2DM is also supported by a number of clinical studies showing associations between low rates of remission with SSRI treatment and T2DM (Anderson et al, 2010;Bryan et al, 2010;Gois et al, 2014). At the molecular levels, it is possible that the basal hypersensitivity of the 5-HT 1A autoreceptor played an important role in the escitalopram non-response by hindering its ability to enhance 5-HT levels in the hippocampus.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the effects of HFD, only one study reported that unpredictable chronic mild stress-induced behavioural changes were all reversed by fluoxetine in STD-fed mice but not in HFDfed mice (Isingrini et al, 2010). SSRI non-response in T2DM is also supported by a number of clinical studies showing associations between low rates of remission with SSRI treatment and T2DM (Anderson et al, 2010;Bryan et al, 2010;Gois et al, 2014). At the molecular levels, it is possible that the basal hypersensitivity of the 5-HT 1A autoreceptor played an important role in the escitalopram non-response by hindering its ability to enhance 5-HT levels in the hippocampus.…”
Section: Figurementioning
confidence: 99%
“…These pharmacological agents, including escitalopram or sertraline, are effective in treating MD in patients with T2DM (Williams et al, 2007;Gehlawat et al, 2013). However, other clinical studies have led to the opposite conclusions (Anderson et al, 2010;Gois et al, 2014), as a significant proportion of patients with T2DM suffering from MD do not achieve remission with SSRI treatment. Among the factors that might explain such a non-response to antidepressant drugs, patient age, the severity of the psychiatric/metabolic disorder or the ability of 5-HT related antidepressant drugs to further destabilize glucose homeostasis (Ghaeli et al, 2004;Raeder et al, 2006;Williams et al, 2007) are possible explanations.…”
Section: Introductionmentioning
confidence: 99%
“…As early as the 1980s, psychotherapy researchers have observed that the bulk of symptomatic improvement occurs within the 1st month of therapy, with 60% of total improvement in cognitive behavioral therapy for depression occurring by Week 4 (Rush, Kovacs, Beck, Weissenburger, & Hollon, ). Since then, numerous other studies have reported early response patterns across different mental health problems and psychological therapies (Bell, Waller, Shafran, & Delgadillo, ; Bradford et al, ; Delgadillo et al, ; Doyle, Le Grange, Loeb, Doyle, & Crosby, ; Gois et al, ; Hunnicutt‐Ferguson, Hoxha, & Gollan, ; Rubel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, numerous randomized controlled trials have shown that IPT is indeed effective in the treatment of depression (3), that it may be more effective than other psychotherapies for depression (4,5), that it may prevent relapse after successful treatment of depression (3), that it may prevent the onset of major depressive disorders in those with subthreshold depression (6), and that it is also effective in specific target groups, such as adolescents (7,8), older adults (9), and patients with a somatic disorder (10)(11)(12).…”
mentioning
confidence: 99%